Triboelectric nanogenerator/supercapacitor in-one self-powered textile based on PTFE yarn wrapped PDMS/MnO2NW hybrid elastomer. (June 2021) - Mao, Yongyun; Li, Yong; Xie, Jiyang; Liu, Huan; Guo, Changjin; Hu, Wanbiao
Abstract: Triboelectric nanogenerator/supercapacitor (TENG-SC) is believed to have great potential for wearable/portable bio-motion energy harvesting/storage electronics, but many TENGs could rarely be satisfactory to wearable electronics because of their poor wearability and complex configurations. Herein, a round-tripping-knitting strategy is devised to directly knit flexible PTFE yarn closing around polydimethylsiloxane/MnO2 nanowire (PDMS/MnO2 NW)-coated conductive carbon cloth yarns (CCT@PDMS/MnO2 NW) that can be used as wearable TENG textile to harvest bio-motion energy. Superior power generation performance was obtained by modulating the dielectric permittivity of PDMS/MnO2 NW elastomer based on variations in the mass-loading of MnO2 NW. The obtained TENG textile can convert various forms of bio-motion energy into electrical signal and the maximum output voltage of about 380 V can be obtained and easily light up 200 serially connected LEDs. Additionally, all-solid-state yarn-type asymmetric supercapacitor was woven with TENG and act as energy storage unit, which demonstrates high volumetric energy density and excellent cyclic stability. Because of the flexible all yarn-type structure of the entire system, the SC and TENG can be easily woven into cloth to continuously harvest and store bio-motion energy, which demonstrates great convenience and immense applications as wearable, lightweight, comfortable continuous bio-motion energy harvesting/storage device and versatile pressure sensing. Graphical Abstract: ga1 Highlights: A wearable integrated energy conversion (TENG) and storage system (SC) in-one textile is developed. The novel TENG textile was first constructed via knitting PTFE yarn wrapped PDMS/MnO2 NW elastic yarn. The TENG textile can harvest ubiquitously biomechanical energy and light up 200 LEDs. The obtained textile electronic can behave as a versatile pressure sensing.